An improved silver staining procedure for schizodeme analysis in polyacrylamide gradient gels - Gonçalves, Antonio M. (1990)
Fundação Oswaldo Cruz. Instituto Oswaldo Cruz. Departamento de Bioquímica e Biologia Molecular. Rio de Janeiro, RJ, Brasil.